Фітотерапія психоемоційних розладів у хворих на вегетативну дисфункцію - Демченко, Аліна Вікторівна; Demchenko, A. V. (My University, 2016)
У статті розглянуті патогенетичні та фармакотерапевтичні аспекти психоемоційних розладів у хворих на вегетативну дисфункцію в лікарській практиці. Проаналізовані сучасні критерії вибору адекватного фітотерапевтичного засобу для корекції цих розладів. Детально розглянуті переваги використання та обґрунтовано застосування фітопрепарату ГеніусПлюс, як оптимального засобу лікування тривожно-депресивних розладів, інсомнії і когнітивних порушень у хворих на вегетативну дисфункцію. Pathogenetic and therapeutic aspects of psycho-emotional disorders in patients with autonomic dysfunctions were represented in the article. The autonomic dysfunction syndrome is associated with many somatic diseases and becomes an interdisciplinary problem that is of great interest for various medical specialists because it is still not clear whether it is a certain disease or risk factor, that is predictor of hypertension, atherosclerosis and coronary heart disease. The autonomic disorders spectrum is extremely varied and is determined by genetic factors (peculiarities of the mental type and autonomic system functioning, autonomic susceptibility of one or another system) and by neurotization causes (stress, intoxication, fatigue, occupational hazards, somatic disease etc.). One of the most frequent autonomic syndrome manifestation is psychoemotional disbalance which is usually hardly tolerated by patients, significantly affects their life quality and increases the pathogenic vicious circle of stress-induced disorders of the central nervous system was discussed in the article. The autonomic syndrome treatment is difficult because there are many unsolved problems due to the lack of highly efficient methods that provide long-term condition stabilization or full recovery. The psycho-emotional symptoms that may be present even after control introduction over somatic symptoms, cause the greatest discomfort to the patient with autonomic syndrome. Therefore, the autonomic syndrome therapy with asthenic or anxiety-depressive syndromes should not be restricted only by somatic disorders, and should include correction of psychoemotional disorders, even of sub-threshold level.
Phytotherapy of psycho-emotional disorders in patients with autonomic dysfunction
Keywords: вегетативна дисфункція; тривожно-депресивні розлади; інсомнія; когнітивні порушення; фітотерапія; ГеніусПлюс; autonomic dysfunction; anxiety and depressive disorders; insomnia; cognitive disorders; phytotherapy; GeniusPlus